You were never lovelier - Kern, Jerome 1885-1945; Mercer, Johnny 1909-1976; Harline, Leigh 1907-1969 (Columbia TriStar Home Entertainment, 2004)
The Acunas family is a family of tradition. The family holds the ritual of making sure that their daughters get married in order of age. When the second daughter does not follow the tradition quick enough her sister resort to finding her a lover